Analysis and design of directive antenna using frequency selective surface superstrate - Siti Rohani Tajuddin; S. N. Azemi; P. J. Soh; C.B.M. Rashidi; A Abdullah Al-Hadi (Institute of Advanced Engineering and Science, 2019)
The design of directive antenna using Frequency Selective Surface (FSS) superstrate is proposed in this project. The suitable design FSS as superstrate layer is very important to enhance the high directivity and narrow bandwidth on the antenna. By using the FSS layer to design the superstrate layer, there are able to determine the reflection coefficient accordingly to the desired frequency.